Brand Positioning Criterions and Consumers Reaction - Mobile Phone Brand Preferences in Coimbatore City - B. Karthikeyan, (European Economic Letters (EEL), 2024)
Brand position creates an image for a particular product of a seller, support them in differentiating from the competitions products, spell out unique features of a products and create a buyer segment for a product. BP is more associated with convincing the buyers to accept a product launched or marketed by creating a perception, attitude, by fixing a fair or premium price and likeness for a brand. The study convey the message that price sensitive attitude expressed by the consumers generally influences their brand selection and repurchase of an advanced model of mobile phones. Sample population falling in the age group of 21-40 years (72.35 per cent) with the family income of Rs.60001 to Rs.75000 (32.71 per cent) prefer buying basic or budgeted smartphones that supports calling, talking, participation in social media, watching movies etc., (79.50 per cent). Approximately 53.60 per cent respondents’ use Android based OS and 80 per cent of the population prefer buying smartphones within Rs.10000 to Rs.20000. High end product like Apple I phones, Mortola and Oppo are purchased keeping the brand image in the mind i.e., prestigious value. Samsung, Lenovo, Micromax and Asus and Lava are purchased based on the flexible price ranges. These brands are also preferred by the buyers based on its in-build features, product availability and durability.